Amiodarone or lidocaine for cardiac arrest: A systematic review and meta-analysis. (October 2016) - Sanfilippo, F.; Corredor, C.; Santonocito, C.; Panarello, G.; Arcadipane, A.; Ristagno, G.; Pellis, T.
Abstract: Background: Guidelines for treatment of out-of-hospital cardiac arrest (OOH-CA) with shockable rhythm recommend amiodarone, while lidocaine may be used if amiodarone is not available. Recent underpowered evidence suggests that amiodarone, lidocaine or placebo are equivalent with respect to survival at hospital discharge, but amiodarone and lidocaine showed higher hospital admission rates. We undertook a systematic review and meta-analysis to assess efficacy of amiodarone vs lidocaine vs placebo. Methods: We included studies published in PubMed and EMBASE databases from inception until May 15th, 2016. The primary outcomes were survival at hospital admission and discharge in OOH-CA patients enrolled in randomized clinical trials (RCT) according to resuscitation with amiodarone vs lidocaine vs placebo. If feasible, secondary analysis was performed including in the analysis also patients with in-hospital CA and data from non-RCT. Results: A total of seven findings were included in the metanalysis (three RCTs, 4 non-RCTs). Amiodarone was as beneficial as lidocaine for survival at hospital admission (primary analysis odds ratio—OR 0.86–1.23, p = 0.40) and discharge (primary analysis OR 0.87–1.30, p = 0.56; secondary analysis OR 0.86–1.27, p = 0.67). As compared with placebo, survival at hospital admission was higher both for amiodarone (primary analysis OR 1.12–1.54, p < 0.0001; secondary analysis OR 1.07–1.45, p < 0.005) and lidocaine (secondary analysis only OR 1.14–1.58, p = 0.0005). With regards to hospital discharge there were no differences between placebo and amiodarone (primary outcome OR 0.98–1.44, p = 0.08; secondary outcome OR 0.92–1.33, p = 0.28) or lidocaine (secondary outcome only OR 0.97–1.45, p = 0.10). Conclusions: Amiodarone and lidocaine equally improve survival at hospital admission as compared with placebo. However, neither amiodarone nor lidocaine improve long-term outcome.